Innovation budgeting over the business cycle and innovation performance - Martin Hud; Christian Rammer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
The global economic crisis of 2008/2009 hit many firms hard. Faced with rapidly declining sales and highly uncertain economic prospects, firms had to cut costs and reconsider their business strategies. With respect to innovation, cost cutting often means to stop or underresource innovation projects which may harm a firm's long-term competitiveness. Firms may therefore refrain from reducing innovation budgets during crises but rather deliberately allocate more resources to innovation activities in order to update their product portfolio for the following recovery. Our analysis examines the effects of changes in innovation budgets during the most recent economic crisis on firms' post-crisis innovation performance. Based on firm-level panel data from the German Innovation Survey covering the period 2006 to 2012, we find a positive effect of crisis adjustment. Raising the ratio of innovation expenditure to sales does increase subsequent sales of market novelties, but not of product imitations. Our findings are dependent upon the way business cycle effects are measured, however. While the results hold for macroeconomic business cycle indicators (change in real GDP), they do not for demand changes in a firm's primary sales market. This may imply that lower opportunity costs of innovation during an economic crisis are transferred into higher post-crisis new product sales by firms in markets less strongly affected by the crisis.
urn:nbn:de:bsz:180-madoc-393428
Keywords: O31; O32; E32; L25; D22; 330